APPROXIMATING FIXED POINTS OF THE NEW SP*-ITERATION FOR GENERALIZED α-NONEXPANSIVE MAPPINGS IN CAT(0) SPACES - Temir, S.; Korkut, O. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2021)
In this paper, we study the convergence of the newly defined SP*-iteration to fixed point for the generalized α-nonexpansive mappings in CAT(0) spaces. Our results improve and extend some recently results in the literature of fixed point theory in CAT(0) spaces.